Chameleons and other quick-change artists - Simon, Hilda (New York : Dodd & Mead, 1973)
Describes the characteristics and behavior of a variety of creatures with the ability to change colors rapidly, discussing psychological, as well as physiological or biochemical, explanations for the phenomenon.
Keywords: Color of animals -- Juvenile literature; Animal behavior -- Juvenile literature